2022
DOI: 10.3390/toxics11010036
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Photodynamic Antimicrobial Chemotherapy on the Microbiome, Neuroendocrine and Immune System of Crustacean Post Larvae

Abstract: Photodynamic antimicrobial chemotherapy (PACT), employing a combination of light and natural photosensitizer molecules such as curcumin, has been accepted as a safe modality for removing aquatic pathogens which cause diseases such as cholera in humans and vibriosis in aquatic animals. Curcumin and its photodegradation products are generally considered as safe to animals, but the impact of reactive oxygen species (ROS) generated by these products on the growth and survival of organisms at a cellular level has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The current study indicated that the photoexcited curcumin up to 50 µM did not induce any toxic effects to the live feed Artemia nauplii. Our previous studies reported irregular expression of neuroendocrine hormone genes in the post larvae of Penaeus monodon on exposure to photoexcited curcumin but there was no mortality even at 50 µM (Abdulaziz et al, 2022). The 5 µM concentration of curcumin could kill more than 90 % of the associated bacteria, without inducing any toxic effects to Artemia nauplii.…”
Section: Efficiency Of Pact In Disinfecting Live Feedmentioning
confidence: 92%
See 1 more Smart Citation
“…The current study indicated that the photoexcited curcumin up to 50 µM did not induce any toxic effects to the live feed Artemia nauplii. Our previous studies reported irregular expression of neuroendocrine hormone genes in the post larvae of Penaeus monodon on exposure to photoexcited curcumin but there was no mortality even at 50 µM (Abdulaziz et al, 2022). The 5 µM concentration of curcumin could kill more than 90 % of the associated bacteria, without inducing any toxic effects to Artemia nauplii.…”
Section: Efficiency Of Pact In Disinfecting Live Feedmentioning
confidence: 92%
“…Photodynamic therapy is comparable with antibiotics in terms of its fast action and broad spectrum, and the lack of resistance development is an additional advantage. Photodynamic antimicrobial chemotherapy with a wide range of activity profile against viruses and bacteria is advantageous for its applications in aquaculture (Abdulaziz et al, 2022;Malara et al, 2019).…”
Section: Introductionmentioning
confidence: 99%